The International Criminal Court: An Analytical Study - Emtenan Mohammed Ali Ahmed; Ahmed Salim Ataya (International Journal of Law Research and Studies, 2025)
All laws agree on the sanctity of the right to life, emphasizing its respect, preservation, and protection. To safeguard human life from extinction and protect the world from destruction, the international community requires a fair criminal justice system. This need became especially pressing after international wars, leading to the emergence of the idea of establishing a permanent International Criminal Court (ICC). The primary goal of the ICC is to prevent the impunity of brutal attacks and crimes against humanity.  In 1998, a pivotal conference was held in Rome, Italy, where the establishment of the International Criminal Court was formalized. This court marked a glimmer of hope for the victims of oppression and injustice worldwide. Unlike the International Court of Justice, which handles state matters, the ICC focuses on individual criminal responsibility. While its jurisdiction is limited to individual cases, this does not diminish the court’s significance. The ICC holds individuals, including leaders who issue orders for crimes such as war crimes, crimes against humanity, genocide, and aggression, accountable for their actions. Additionally, field commanders who oversee such atrocities are also held responsible. The purpose of establishing international criminal courts is to monitor and punish perpetrators of serious international crimes. The jurisdiction of these courts is defined by international law and is outlined in agreements designed to address international crimes that pose a severe threat to global peace and security.
Keywords: International Criminal Court; Rome Statute; Crimes; Subject-Matter Jurisdiction